What Do Sources Say about Agricultural Slavery (and Why Don’t They Say More)? A Study on Legal Sources for Early Islamic Ifrīqiya - Bosanquet, Antonia (Journal of the economic and social history of the Orient, 2025)
This study examines the evidence for agricultural slavery in early Islamic Ifrīqiya and relates it to the existing historiography on the topic. It argues that legal texts, which are used more than other sources to understand slavery and slave labor, are of limited value for understanding agricultural slavery and that references in other text genres should be given more weight. If we assess these references independently of a criterion formed by legal discussions about slavery they can be seen as evidence for the widespread and sometimes large-scale nature of slave labor in rural contexts, which is a model that has not received much support in recent historiography. This article focuses on early Islamic Ifrīqiya but as the evaluation of legal sources is also relevant for texts produced outside the Islamic West, its findings are relevant for discussions of agricultural slavery in other parts of the early Islamic Empire as well.